MANAGEMENT OF HUMAN RESOURCES IN IMPROVING THE QUALITY OF THE FLAGSHIP LANGUAGE PROGRAM AT NURUL JADID HIGH SCHOOL, PAITON DISTRICT, PROBOLINGGO REGENCY - Rahman, Faisal; Ummah, Nur Ittihadatul (LPPM Universitas Malikussaleh, 2024)
Human resource planning (HR) is the first and strategic step in supporting the quality of the language excellence program at Nurul Jadid High School. This process involves analyzing human resources needs by identifying the number, type, and competencies needed to support the program. The main focus of this study is to ensure the existence of educators who have adequate language skills (Arabic, English, and Mandarin) and superior pedagogical skills. Human resource placement is an important stage in workforce management, especially in flagship programs such as the Language Program at Nurul Jadid High School. The evaluation of work values aims to assess the effectiveness and efficiency of educators in supporting language excellence programs. Structured assessment can provide valuable feedback for improvement